FACTORS ASSOCIATED WITH PERINEAL WOUND HEALING AMONG POSTPARTUM WOMEN AFTER VAGINAL DELIVERY IN PRIMARY HEALTH CARE - Nurdahliana; Sarinah Siregar; Nova Ratna Dewi; Rina Julianti; Marlina; Meliani Sukmadewi Harahap (Pena Cendekia Insani, 2026)
Perineal trauma following vaginal delivery is a common postpartum complication that may delay recovery and increase the risk of adverse maternal outcomes. This study examined factors associated with perineal wound healing among postpartum women in Bireuen District, Indonesia. A cross-sectional study was conducted from December 2025 to April 2026 involving 120 postpartum women assessed 10-14 days after normal vaginal delivery. Participants were recruited consecutively from the Jeumpa, Gandapura, and Kutablang Primary Health Centers. Perineal wound healing was evaluated through clinical observation, while demographic, behavioral, psychosocial, and cultural characteristics were collected using structured questionnaires. Associations were analyzed using chi-square tests and multivariable logistic regression. In bivariate analyses, type of perineal tear, personal hygiene, cultural practices, and family support were significantly associated with perineal wound healing. In the multivariable model, family support (AOR = 31.21; 95% CI: 2.55-382.12; p = 0.007) and personal hygiene (AOR = 27.74; 95% CI: 2.41-319.86; p = 0.008) remained significantly associated with favorable wound healing. The wide confidence intervals indicate substantial uncertainty in the estimated effect sizes. These findings suggest that personal hygiene and family support are associated with perineal wound healing; however, the cross-sectional design precludes causal inference, and longitudinal studies are needed to confirm these associations.